Avaliação bidimensional do transporte do canal radicular após preparos apicais largos com sistemas rotatórios, reciprocantes e adaptativos - Vieira, Vânia Cristina Gomes (2016)
This study evaluated the ability of rotary (ProTaper Universal [PTU] and ProTaper Next [PTN]), reciprocating (Reciproc [R] and WaveOne [WO]) and adaptive (Twisted File Adaptive [TFA]) systems in maintaining the original profile of root canal anatomy after apical preparations up to size 40. Fifty curved root canals simulated in clear resin blocks were randomly assigned to 5 groups (n = 10) according to the instrumentation system: PTU, PTN, R, WO and TFA. Ten blocks were used as a control group where no instrumentation was performed. Color stereomicroscopic images from each block were taken exactly at the same position before and after instrumentation. All image processing and data analysis were performed with an open-source program (Fiji). Evaluation of canal transportation was obtained for 2 independent canal regions: straight and curved portions. Univariate analysis of variance and Tukey Honestly Significant Difference were used and a cut-off for significance was set at α = 5%. Instrumentation systems significantly influenced canal transportation (P = .000). Transportation was higher at the curved canal portion (P = .000). For both canal levels, TFA system induced the lowest mean of canal transportation followed by PTN, R, WO and PTU systems. However, a significant interaction between instrumentation system and root canal level was also found; at the straight portion, R and TFA systems produced similar canal transportation (P > .05), which was significantly lower than the WO, PTN and PTU systems (P = .000); at the curved part, TFA system resulted in the lowest canal transportation followed by PTN, R, WO and PTU systems (P = .000). TFA system produced overall less canal transportation than the others systems. The multi-file rotary system ProTaper Universal caused more canal transportation then the other tested systems.